Crítica sistémica: un enfoque hermenéutico del fenómeno arquitectónico (2014)
Systemic criticism analyzes the way how the addressee interprets an architectural phenomenon through three perspectives: cognitive, semiotic, and symbolic. Its purpose is to propose a critical view under a transdisciplinary, open, and holistic standpoint, in accordance to the context in which the object of design is currently generated. It picks up from hermeneutics the conception of an interpretation supported in three stages: prefiguration, configuration, and refiguration; this last part in three dimensions: logic, ethics, and aesthetics, in order to incorporate a new paradigm in which the architectural phenomenon has transcend tectonics (formal and funtional) and gets closer to the anthropological realm. This study concludes with the implementation of a proposal, whose results show the richness of a hermeneutical approach that transcends the object by perceiving it as a phenomenon